Increased ventilation in runners during running as compared to walking at similar metabolic rates - Berry, M. J.; Dunn, C. J.; Pittman, C. L.; Kerr, W. C.; Adair, N. E. (European Journal of Applied Physiology, 1996)
At similar levels of carbon dioxide production (VCO2) and oxygen consumption (VO2), runners have been shown to have a greater minute ventilation (VE) during running as compared to walking. The mechanism responsible for these differences has yet to be identified. To determine if these differences are a result of differences in acid-base status, potassium (K+), norepinephrine and/or epinephrine levels, seven well-trained runners completed walk and run tests at similar VO2 and VCO2 levels. The occurrence of entrainment of the breathing and stride frequencies during both walking and running was also determined. VE was significantly greater during the run as compared to the walk, 73.7 (2.2) versus 68.6 (2.0) l.min-1, respectively, despite the similarity in VO2 and VCO2 levels. Alveolar ventilation was not significantly different between the run and the walk, 60.4 (4.7) versus 59.6 (4.4) l.min-1, respectively. Dead space ventilation was found to be significantly greater during running as compared to walking, 13.3 (3.2) versus 9.0 (4.7) l.min-1, respectively. The increases in VE were due to increases in breathing frequency and decreases in tidal volume during the run as compared to the walk. Arterial partial pressures of CO2 (PaCO2) were not significantly different when comparing walking and running to rest values nor when comparing walking and running. Arterial pH was significantly lower during walking as compared to rest and running. Bicarbonate levels were significantly lower during walking as compared to rest. Lactate was significantly greater during walking as compared to rest and to running. K+ levels were significantly higher during walking and running as compared to rest. Epinephrine and norepinephrine levels were not significantly different between running and walking. During the walk, six of the seven subjects entrained their breathing frequency to the stride frequency, and during the run three of the seven subjects demonstrated entrainment. Results from this investigation do not support mediation of VE under the present experimental conditions by changes in arterial levels of humoral factors previously shown to influence VE.